2016
DOI: 10.1038/ncomms12342
|View full text |Cite|
|
Sign up to set email alerts
|

A protein-truncating R179X variant in RNF186 confers protection against ulcerative colitis

Abstract: Protein-truncating variants protective against human disease provide in vivo validation of therapeutic targets. Here we used targeted sequencing to conduct a search for protein-truncating variants conferring protection against inflammatory bowel disease exploiting knowledge of common variants associated with the same disease. Through replication genotyping and imputation we found that a predicted protein-truncating variant (rs36095412, p.R179X, genotyped in 11,148 ulcerative colitis patients and 295,446 contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 37 publications
0
51
0
4
Order By: Relevance
“…NFID cases were jointly called with a collection of Finnish individuals collected as part of the Sequencing Initiative Suomi (SISU)study (www.sisuproject.fi). The sequence data processing and variant calling has been described previously 21 . See Supplemental Note 1 for descriptions of cohorts used in the current study.…”
Section: Exome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…NFID cases were jointly called with a collection of Finnish individuals collected as part of the Sequencing Initiative Suomi (SISU)study (www.sisuproject.fi). The sequence data processing and variant calling has been described previously 21 . See Supplemental Note 1 for descriptions of cohorts used in the current study.…”
Section: Exome Sequencingmentioning
confidence: 99%
“…We filtered samples with estimated contamination > 3% (n= 590), chimeric reads > 3% (n= 51), as well as those samples significantly deviating from other samples within each project/batch on selected metrics (transition/transversion ratio, insertion/deletion ratio, heterozygous / homozygous variant ratio, number of singletons, n=243) and finally indluced only those with empirically confirmed >=99% Finnish ancestry (described in Rivas et al 21 ).…”
Section: Exome Sequencingmentioning
confidence: 99%
“…We performed phenome-wide analyses and directly measured the effect of homozygous carriers, commonly referred to as "human knockouts," across medical phenotypes for genes implicated to be protective against disease or associated with at least one phenotype in our study and found several genes with strong pleiotropic or non-additive effects. Our results illustrate the importance of protein-truncating variants in a variety of diseases.Protein-truncating variants (PTVs), genetic variants predicted to shorten the coding sequence of genes, are a promising set of variants for drug discovery since identification of PTVs that protect against human disease provides in vivo validation of therapeutic targets 1,2,3,4 . Although tens of thousands of standing germline PTVs have been identified 5,6 , their medical relevance across a broad range of phenotypes has not been characterized.…”
mentioning
confidence: 99%
“…The increase in power differs across phenotypes depending on the fraction of total cases that are added by including cases ascertained from questionnaire data. Notably, identifying additional cases causes a larger increase in the power to detect rare protective variants which are especially useful for identifying therapeutic targets [14,17,18,23] .…”
Section: Gwas Based On Hospital Records or Questionnaire Responsesmentioning
confidence: 99%
“…However, the degree to which proxy phenotyping attenuates effect sizes relative to traditional GWAS and the statistical power benefits of using GWAX in biobanks has not been explored. Estimating the agreement between digital phenotyping, GWAX, and traditional GWAS is important for understanding the extent to which these new phenotyping strategies may help uncover the genetic basis of human diseases and empower the generation of therapeutic hypotheses by, for instance, identifying strong acting protein-truncating variants [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%